Provenance analysis of Devonian peripheral foreland basins in SW Gondwana, case of the Gualilán Group, Precordillera Argentina - Arnol, Jonatan Ariel (2020)
We carried out a sedimentary provenance analysis of the Devonian Gualilan Group, Central Precordillera of western Argentina, focusing on the siliciclastic record of the Talacasto (Lower Devonian) and the Punta Negra (Lower-Middle Devonian) formations. Provenance is determined based on petrography, heavy minerals, whole-rock geochemistry, Sm–Nd isotopes, and U–Pb detrital zircon dating. Sandstones are composed of quartz, feldspar, and metamorphic and plutonic lithoclasts. The Gualilan Group underwent moderate weathering indicated by CIA values and Th/U ratios below 76 and 4.9, respectively. Th/Sc, Zr/Sc, Cr/V and La/Th ratios, negative Eu-anomalies and REE patterns point to felsic source compositions. The heavy minerals and zircon morphologies indicate that high-grade metamorphic and igneous rocks provided the bulk of detritus. TDM ages between 1.40 and 1.46 Ga and eNd(t) values ranging from − 9.21 to − 11.13 constrain the signature of the sources. U–Pb detrital zircon ages for the Talacasto Formation are equally distributed between the Famatinian (Late Cambrian–Late Devonian), Pampean–Brazilian (Neoproterozoic–Early Cambrian) and Grenvillian-Sunsas (Mesoproterozoic) orogenic cycles. Detrital zircon ages of the Punta Negra Formation were dominantly supplied from Mesoproterozoic rocks, linked to the Grenvillian-Sunsas orogeny. The data indicate a provenance from rocks located eastwards of the basin represented by the basement of the Pampean Ranges. The peripheral foreland basin developed during the post-collisional regime that followed the accretion of Cuyania against Gondwana. Whereas eastern and western Pampean Ranges provided detritus to the Talacasto Formation, the Punta Negra Formation was sourced by the western Pampean Ranges, implying exhumation and erosion of such basement during the Devonian.